Analysis of Selling Price in Profit Planning in Dishcaven Malang - Alfian Achmad Zulfikar; Dwi Anggarani; Khojanah Hasan (CV. Ulil Albab Corp, 2024)
This research was conducted to find out whether setting selling prices at the Dishcaven Malang convection business is effective for profit planning. The data analysis method used is calculating profit determination using the full costing method. Based on the calculation results, it was found that the product selling price applied by Dishcaven turned out to have a difference with the selling price determined using a full costing approach with a mark up value of 24%. Apart from that, the calculation for determining the selling price at Dishcaven turns out to be lower than the total selling price calculated based on the formula for determining the selling price which is determined with a mark up value of 24%, so the profit obtained is not yet maximized. Through the results of this research, Dishcaven should be able to determine product selling prices based on factors that are directly related to the entire product purchase price, sales costs, expected profit amount so that the right selling price is obtained and Dishcaven should be more precise in its calculations. The selling price of the company's products with the correct mark up percentage includes operating costs and the desired profit amount using accounting approaches so that the profit obained is maximized.